Study the Effectivity Learning Outcomes of 2 type Learning Cooperative Methods (Make a Match & Scramble ) At the Junior high school Students in Labuhanbatu District || Studi Efektifitas Hasil Belajar 2 Metode Belajar Kooperatif (Tipe Make a Match & Tipe Scramble ) Pada Siswa SMP di Kabupaten Labuhanbatu - Lilianti, Lilianti (Universitas Labuhanbatu, 2021)
This study aims to determine the comparison of student learning outcomes in the application of the Make a match learning method with the Scramble method on the subject matter of the Expression System. The research design used was a quasi experiment with a pretest-postest experiment group design. In the experimental class I who were taught using the Make a Match method the average score of student learning outcomes was 53,56 and the increase in the average score of student learning outcomes was 89,04. In the experimental class II which was taugh using the Scramble method the average score of student learning outcomes was 52,92 and the increase in the average score was 83,60. The results showed that there were differences in student learning outcomes between the experimental class I and experimental class II. These results indicate that the use of the Make a match learning method is more effective in improving student learning outcomes compared to the Scramble learning method in this study in second class (VIII) of Yapendak Ajamu Junior High School in 2019/2020 Learning Year.Penelitian ini bertujuan untuk mengetahui perbandingan hasil belajar siswa pada penerapan metode pembelajaran Make a match dengan metode Scramble pada materi pokok Sistem Eksresi. Desain penelitian yang digunakan adalah quasi experiment dengan rancangan kelompok pretest-postest experiment group design. Pada kelas eksperimen I yang dibelajarkan dengan menggunakan metode Make a match skor rata-rata hasil belajar siswa adalah 53,56 dan kenaikan skor rata-rata hasil belajar siswa sebesar 89,04. Pada kelas eksperimen II yang dibelajarkan dengan menggunakan metode Scramble skor rata-rata hasil belajar siswa adalah 52,92 dan kenaikan skor rata-rata 83,60. Hasil penelitian menunjukkan bahwa terdapat perbedaan hasil belajar siswa antara kelas eksperimen I dan kelas eksperimen II. Hasil tersebut menunjukkan bahwa penggunaan metode pembelajaran Make a match lebih efektif untuk meningkatkan hasil belajar siswa dibandingkan dengan metode pembelajaran Scramble dalam penelitian ini dikelas VIII SMP Swasta Yapendak Ajamu Tahun Pembelajaran 2019/2020